Combined effects of PEG hydrogel elasticity and cell-adhesive coating on fibroblast adhesion and persistent migration - Missirlis, Dimitris; Spatz, Joachim P. (Biomacromolecules, 2014)
The development and use of synthetic, cross-linked, macromolecular substrates with tunable elasticity has been instrumental in revealing the mechanisms by which cells sense and respond to their mechanical microenvironment. We here describe a hydrogel based on radical-free, cross-linked poly(ethylene glycol) to study the effects of both substrate elasticity and type of adhesive coating on fibroblast adhesion and migration. Hydrogel elasticity was controlled through the structure and concentration of branched precursors, which efficiently react via Michael-type addition to produce the polymer network. We found that cell spreading and focal adhesion characteristics are dependent on elasticity for all types of coatings (RGD peptide, fibronectin, vitronectin), albeit with significant differences in magnitude. Importantly, fibroblasts migrated slower but more persistently on stiffer hydrogels, with the effects being more pronounced on fibronectin-coated substrates. Therefore, our results validate the hydrogels presented in this study as suitable for future mechanosensing studies and indicate that cell adhesion, polarity, and associated migration persistence are tuned by substrate elasticity and biochemical properties.
Published: November 25, 2013
Gesehen am 13.10.2020